Sorption kinetics of heavy metals from aqueous solution using Spirogyra sp.: a microcosm study - Evi Susanti; Mey Ristanti Widoretno; Dian Oktaviyani; Fajar Sumi Lestari; Nasrul Muit; Riky Kurniawan; Eva Nafisyah (BRIN Publishing, 2023)
Understanding the mechanisms by which algae communities respond to disturbances in the lotic aquatic environment that is polluted by heavy metals is important, considering that algae is a biotic component of waters that acts as a producer in the aquatic food chain which has the potential to bio-magnify. This study examines the influence of time, biomass weight, heavy metal concentration, sorption capacity, and efficient removal on epilithic periphyton as a bio-accumulator of Cr, Pb, and Ni. The experiment was conducted on a laboratory scale using a canal system with a length and width of 1.2 and 1.0 meters, respectively. The canal system contains 132 L of water, has a 1.2 m2 substrate and periphyton area, a depth of 0.09 – 0.10 m, and a current flow rate of 0.04 – 0.06 m/s. The dissolved Cr6+ initial concentration in the medium was 1.64 mg/L, Pb2+ and Ni2+ concentrations were 1.4 mg/L, and the adsorption process was studied for 24 hours. Based on microscope observations and functional group interpretation utilizing infrared spectra (FTIR), the periphyton community is dominated by Spirogyra sp., which has hydroxyl (O-H), carboxyl (C-H), and carbonyl (C-C and C=O) functional groups with the ability to binding heavy metals. The remaining quantities of Cr, Pb, and Ni in water were 0.43 mg/L (removal 69.29%), 0.05 mg/L (96.43% removal), and 0.03 mg/L (97.86% removal). Periphyton has a maximal sorption capacity of 1.019 mg Cr/g, 1.97 mg Pb/g, and 1.92 mg Ni/g. The sorption kinetics of Cr, Pb, and Ni follow a pseudo-second-order model with k2 = 1.686 x 10-2 g/mg.min for Cr, 4.516 x 10-3 g/mg.min for Pb, and 2.259 x 10-2 g/mg.min for Ni, with R2 of 0.965 for Cr and 0.971 for Pb and 0.972 for Ni. Periphyton can potentially play a role as a bio-accumulator in lotic habitats, adsorbing Cr, Pb, and Ni ions, according to this study.